2022
DOI: 10.1177/20420986221143266
|View full text |Cite
|
Sign up to set email alerts
|

Safety of triazole antifungals: a pharmacovigilance study from 2004 to 2021 based on FAERS

Abstract: Background: Triazole antifungals are widely used as broad-spectrum antifungal activity; however, there are many undetected and unreported adverse events (AEs). Methods: Data from the Food and Drug Administration Adverse Event Reporting System (FAERS) from the first quarter (Q1) of 2004 to the third quarter (Q3) of 2021 were selected for disproportionality analysis to assess the connection between antifungal triazoles, and AEs and important medical events (IMEs). Results: A total of 22,566 records associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…In contrast, no statistically significant associations between antivirals versus all other drugs or antivirals versus antibiotics were observed for IC hemorrhages. Some researchers suggest that if the lower limit of the 95% CI of the ROR is greater than 1, the signal should be considered statistically significant, while others propose a cut‐off, where an ROR value of 2 can be used as a threshold 26,27 . As there is no universally accepted threshold for drug adverse event association in disproportionality analysis signal detection algorithms, no specific value for such a threshold is used in this study as a safety signal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, no statistically significant associations between antivirals versus all other drugs or antivirals versus antibiotics were observed for IC hemorrhages. Some researchers suggest that if the lower limit of the 95% CI of the ROR is greater than 1, the signal should be considered statistically significant, while others propose a cut‐off, where an ROR value of 2 can be used as a threshold 26,27 . As there is no universally accepted threshold for drug adverse event association in disproportionality analysis signal detection algorithms, no specific value for such a threshold is used in this study as a safety signal.…”
Section: Discussionmentioning
confidence: 99%
“…significant, while others propose a cut-off, where an ROR value of 2 can be used as a threshold. 26,27 As there is no universally accepted threshold for drug adverse event association in disproportionality analysis signal detection algorithms, no specific value for such a threshold is used in this study as a safety signal.…”
Section: Characteristicsmentioning
confidence: 99%
“…Posaconazole isavuconazole, voriconazole and fluconazole antifungals have been linked to dryness, drug rash, hair loss, diarrhoea, lethargy, nausea, and vomiting, as well as a prolonged QT interval [34]. Although isavuconazole has a similar mechanism of action and belongs to the same triazole family as the other four medications, it induces the opposite side effect, such as a shortening of the QT interval.14 Furthermore, itraconazole's boxed warning mentions medication interactions, cardiac consequences, and congestive heart failure (CHF) [35].…”
Section: XIVmentioning
confidence: 99%
“…Triazoles have been demonstrated in the past to raise plasma levels of vinca alkaloids and produce neurotoxicity due to their inhibitory impact on CYP3A4. It is not apparent how triazole antifungals produce neurotoxicity [35].…”
Section: Cause Of Resistancementioning
confidence: 99%
“…After discontinuation of voriconazole, symptoms started to improve within a month and resolved in a year. Voriconazole contains three fluoride atoms, when compared to posaconazole and fluconazole which contain two [1][2][3]. The previous study showed that voriconazole develops hyper-fluorosis, potentially associated with periostitis, whereas other azoles such as fluconazole and posaconazole has lower risk for this condition [4] The most common symptom for voriconazole-associated periostitis is localized diffuse bone pain [5][6][7][8].…”
Section: Diagnosis: Voriconazole-associated Periostitismentioning
confidence: 99%